1982
DOI: 10.1113/jphysiol.1982.sp014099
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte nucleoside transport: asymmetrical binding of nitrobenzylthioinosine to nucleoside permeation sites

Abstract: 1. Nitrobenzylthioinosine is a potent and specific inhibitor of nucleoside translocation in animal cells. Kinetic and inhibitor binding studies were undertaken to clarify how this inhibitor interacts with the nucleoside transporter from human and nucleoside‐permeable type sheep erythrocytes. 2. [3H]nitrobenzylthioinosine inhibition of zero‐trans [U‐14C]uridine influx into nucleoside‐permeable type sheep cells was consistent with simple competitive inhibition (apparent Ki 1 nmol/l). Analysis of results using to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 35 publications
5
41
0
Order By: Relevance
“…This common mechanism of inhibition suggested that the residues involved in dipyridamole binding by hENT1 and CeENT1 may be conserved and was consistent with the results of previous studies that had suggested that the dipyridamole-binding site overlaps with the exofacial permeant binding site of ENT transporters (16,18,39).…”
Section: Discussionsupporting
confidence: 90%
“…This common mechanism of inhibition suggested that the residues involved in dipyridamole binding by hENT1 and CeENT1 may be conserved and was consistent with the results of previous studies that had suggested that the dipyridamole-binding site overlaps with the exofacial permeant binding site of ENT transporters (16,18,39).…”
Section: Discussionsupporting
confidence: 90%
“…NBMPR Binding to BeWo Membrane Fractions-Because [ 3 H]NBMPR binds specifically and with high affinity to functional nucleoside transporters, equilibrium binding analysis has been used extensively as a surrogate marker for the presence of the es transporter protein (1,8,32,33). BeWo membrane fractions collected at different sucrose concentrations were first assayed for NBMPR binding activity at a single concentration (5 nM) under conditions previously shown in studies with intact cells (19) to be sufficient to label over 40% of the high affinity sites.…”
Section: Resultsmentioning
confidence: 99%
“…, which has been used extensively in the characterization of equilibrative nucleoside transport proteins (1,8,32,33), was performed as follows. Membrane preparations, proteoliposomes (ϳ10 g of protein/ml final concentration), and intact nuclei and nuclear membranes (at ϳ40 g of protein/ml) were incubated for 45 min at room temperature with a range of concentrations (0.24 -24 nM) of [ 3 H]NBMPR in either the absence (total binding) or presence (nonspecific binding) of 10 M NBMPR (1-ml final assay volume).…”
Section: Equilibrium Binding Of [ 3 H]nbmpr-high Affinity Binding Of mentioning
confidence: 99%
“…inhibitor) binding site overlaps with the uridine (i.e. permeant) binding site of hENT1 (33)(34)(35). Dipyridamole resistance was seen when Met 33 was changed to Ala in TM1 of hENT1, thereby identifying it as a key residue for dipyridamole interaction with hENT1.…”
Section: Discussionmentioning
confidence: 99%